2011
DOI: 10.1182/blood-2010-09-309955
|View full text |Cite
|
Sign up to set email alerts
|

PTEN deficiency in mast cells causes a mastocytosis-like proliferative disease that heightens allergic responses and vascular permeability

Abstract: Kit regulation of mast cell proliferation and differentiation has been intimately linked to the activation of phosphatidylinositol 3-OH kinase (PI3K). The activating D816V mutation of Kit, seen in the majority of mastocytosis patients, causes a robust activation of PI3K signals. However, whether increased PI3K signaling in mast cells is a key element for their in vivo hyperplasia remains unknown. Here we report that dysregulation of PI3K signaling in mice by deletion of the phosphatase and tensin homolog (Pten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…62 Interestingly, using an animal model in which PTEN can be deleted in an inducible way, Furumoto et al have recently shown that this deletion caused MCs hyperplasia in various organs, which was associated with increased phosphorylation of STAT5 and AKT. 63 Moreover, in another study, Peng et al have reported that PTEN is down-regulated by BCR-ABL1 in an in vivo model of BCR-ABL1-induced CML and that overexpression of PTEN delayed the development of CML and prolonged survival of leukemia. 64 In the same study, it was shown that PTEN suppressed leukemia stem cells and induced cell-cycle arrest of leukemia cells.…”
Section: 61mentioning
confidence: 99%
“…62 Interestingly, using an animal model in which PTEN can be deleted in an inducible way, Furumoto et al have recently shown that this deletion caused MCs hyperplasia in various organs, which was associated with increased phosphorylation of STAT5 and AKT. 63 Moreover, in another study, Peng et al have reported that PTEN is down-regulated by BCR-ABL1 in an in vivo model of BCR-ABL1-induced CML and that overexpression of PTEN delayed the development of CML and prolonged survival of leukemia. 64 In the same study, it was shown that PTEN suppressed leukemia stem cells and induced cell-cycle arrest of leukemia cells.…”
Section: 61mentioning
confidence: 99%
“…Most of these groups used a strategy consisting of generating transgenic mice expressing the Cre recombinase under the control of promoters for MC proteases, such as those for carboxypeptidase A3 ( Cpa3 ) or MC protease 5 ( Mcpt5 ) 167, 168, 172 . Such mice then were crossed with mice in which genes of interest have been “floxed” to delete expression of these gene products in the MCs 168, 173 . Our group mated Cpa3 -Cre mice with mice expressing the floxed survival factor Mcl-1 : the resulting Cpa3-Cre; Mcl-1 fl/fl mice were severely deficient in MCs but had also markedly reduced basophil levels 167 .…”
Section: Mouse Models To Study Mast Cell Functions In Vivomentioning
confidence: 99%
“…Phosphatase and tensin homologue deleted on chromosome ten (PTEN) dephosphorylates PI(3,4,5)P 3 at the 3′ position. Deficiency in PTEN had a very similar effect as the absence of SHIP1 (Furumoto et al, 2011). …”
Section: Signal Transductionmentioning
confidence: 98%
“…Further studies showed that PTEN knockout mice exhibited mast cell hyperplasia in various organs. Selective depletion of PTEN in mast cells revealed that this phenomenon is intrinsic to the mast cell (Furumoto et al, 2011). In this study no changes in mast cell chemotaxis towards antigen and SCF in PTEN-deficient mast cell were found.…”
Section: Chemotaxismentioning
confidence: 99%